A diurnal story of Δ17O( $$\rm{NO}_{3}^{-}$$ NO 3 − ) in urban Nanjing and its implication for nitrate aerosol formation - Yan-Lin Zhang; Wenqi Zhang; Mei-Yi Fan; Jianghanyang Li; Huan Fang; Fang Cao; Yu-Chi Lin; Benjamin Paul Wilkins; Xiaoyan Liu; Mengying Bao; Yihang Hong; Greg Michalski (npj Climate and Atmospheric Science, 2022)
Abstract Inorganic nitrate production is critical in atmospheric chemistry that reflects the oxidation capacity and the acidity of the atmosphere. Here we use the oxygen anomaly of nitrate (Δ17O( $$\rm{NO}_{3}^{-}$$ NO 3 − )) in high-time-resolved (3 h) aerosols to explore the chemical mechanisms of nitrate evolution in fine particles during the winter in Nanjing, a megacity of China. The continuous Δ17O( $$\rm{NO}_{3}^{-}$$ NO 3 − ) observation suggested the dominance of nocturnal chemistry (NO3 + HC/H2O and N2O5 + H2O/Cl−) in nitrate formation in the wintertime. Significant diurnal variations of nitrate formation pathways were found. The contribution of nocturnal chemistry increased at night and peaked (72%) at midnight. Particularly, nocturnal pathways became more important for the formation of nitrate in the process of air pollution aggravation. In contrast, the contribution of daytime chemistry (NO2 + OH/H2O) increased with the sunrise and showed a highest fraction (48%) around noon. The hydrolysis of N2O5 on particle surfaces played an important role in the daytime nitrate production on haze days. In addition, the reaction of NO2 with OH radicals was found to dominate the nitrate production after nitrate chemistry was reset by the precipitation events. These results suggest the importance of high-time-resolved observations of Δ17O( $$\rm{NO}_{3}^{-}$$ NO 3 − ) for exploring dynamic variations in reactive nitrogen chemistry.